A Self‐Recognition Separator for Ion Management to Customize Selective Zn2+ Channels Toward Dendrite‐Free Zinc Metal Anodes - Yingbo Shao; Wen Lu; Tianyu Zhang; Bowen Yin; Bin‐Bin Xie; Jiqiang Ning; Yong Hu (Carbon Energy)
ABSTRACT Aqueous zinc‐ion batteries (ZIBs) are promising candidates for next‐generation energy storage, but the problems related to Zn dendrites and side reactions severely hinder their practical applications. Herein, a self‐recognition separator based on a Bi‐based metal–organic framework (GF@CAU‐17) is developed for ion management to achieve highly reversible Zn anodes. The GF@CAU‐17 has self‐recognition behavior to customize selective Zn2+ channels, effectively repelling SO42– and H2O, but facilitating Zn2+ conduction. The inherent properties of CAU‐17 result in the repulsion of SO42– ions while disrupting the hydrogen bond network among free H2O molecules, restraining side reactions and by‐products. Simultaneously, the zincophilic characteristic of CAU‐17 expedites the desolvation of [Zn(H2O)6]2+, leading to a self‐expedited Zn2+ ion pumping effect that dynamically produces a steady and homogeneous Zn2+ ion flux, and thereby alleviates concentration polarization. Consequently, a symmetric cell based on the GF@CAU‐17 separator can achieve a long lifespan of 4450 h. Moreover, the constructed Zn//GF@CAU‐17//MnO2 cell delivers a high specific capacity of 221.8 mAh g−1 and 88.0% capacity retention after 2000 cycles.